Optimizing English Language Teaching in Elementary School Based on Merdeka Curriculum - Efendi, Tri; Prihantini, Apsari Fajar; Nurhidayah, Sri (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
In globalization and 5.0 industry, English has been a mandatory skill a student hould have. However, at elementary level, the teaching and learning of English seems neglected. It could be revealed from the researchers’ preliminary study in one of the state elementary schools in Menganti, Gresik that the school doesn’t have any English teachers, resulting homeroom teachers or other subject teachers teaching the students. Besides, grammar was still the center of teaching as well as the teachers had much worry about grammar since their basics was not English. On account of that, the researchers conducted a mentorship to optimize the teaching and learning English in Elementary schools. The mentorship program was held in one day due to the limited time. The participants of this program were 12 teachers who taught English in that school. The activity was done by emphasizing on what and how English language teaching focuses on. Later, the material examples were given as a means of presenting language learning. Finally, the question and answer were provided so that the participants of this program could have a better understanding. The program ran smoothly and successfully and the participants seemed enthusiasts